Association of bioelectrical impedance phase angle and nutritional status in patients undergoing pancreaticoduodenectomy - Li, Jialing; Hu, Defu; Yan, Yu; Yu, Mengyu; Hang, Hexing; Qiu, Yudong; Chen, Dayu; Fu, Xu (Frontiers in Nutrition, 2025)
BackgroundVarious tools for nutritional assessment are used in individuals undergoing pancreaticoduodenectomy (PD), causing varying prevalence rates of malnutrition. This may explain the causal link between nutrition status and clinical outcomes. Phase angle (PhA), a derived metric obtained from bioelectrical impedance analysis (BIA) is used to indicate the nutrition status and evaluate disease prognosis. The aims of this study is to investigate the role of PhA in assessing the nutritional status of patients undergoing PD and to propose new strategies for the perioperative nutritional management of these patients.MethodsOne hundred and seventy-three consecutive who underwent PD between March 2023 and September 2024 were evaluated and analyzed retrospectively. Comprehensive nutritional screening, evaluation, and body composition measurements were conducted within the first 48 h after admission. The Spearman correlation analysis was employed to assess the relationship between PhA and nutritional status. Receiver operating characteristic curves (ROC) were generated to assess the capacity of PhA to forecast nutrition risk and determine the cutoff value. The data were categorized into two groups according to the established cutoff value, i.e., the normal PhA group and the low PhA group. We further compared the preoperative nutritional statuses and complications between the two groups.ResultsThis single-center retrospective study demonstrated that PhA positively correlated with body mass index (BMI), albumin (ALB), prealbumin (PAB), body cell mass (BCM), skeletal muscle mass (SMM), fat-free mass (FFM), and skeletal muscle mass index (SMI) (P < 0.001). On the other hand, PhA negatively correlated with age and extracellular water/total body water (ECW/TBW) (P < 0.001). The group identified as at nutritional risk and classified as malnourished group had significantly lower PhA values compared to the well-nourished group (P < 0.001). The ROC curves revealed that the optimal cutoff point of PhA in predicting nutrition risk was 4.85° (AUC: 0.794).ConclusionIn summary, patients undergoing PD with low PhA are more likely to develop malnutrition different degrees. Therefore, PhA may serve as a potential biomarker for preoperative nutritional assessment. While PhA shows utility in nutritional evaluation, it exhibited limited clinical significance for predicting most surgical complications in our cohort.